PENDIDIKAN ANAK USIA DINI (PAUD) PERSPEKTIF PENDIDIKAN ISLAM - Imron, Imron (Universitas Muhammadiyah Magelang, 2011)
Having children is part of the exam Allah gave to us (Surat al-Anfal verse 28). Therefore the child is entrusted to God Almighty and we keep our students in such a way that human beings grow into a useful and always radiate the glory of his personality.The task of parents and teachers in schools in order to education of children is to help children discover and empower potential. This is done since an early age children (since childhood) until the child finds himself and becomes an adult.Olehkarena it pelaksnaan early childhood education conducted in two dimensions, namely (1) Early Childhood Education in the Family and (2) early childhood education in formal education Seeing the two dimensions above, parents and teachers become role in order to develop the potential of children.